The Effectiveness of Georgiana's Podcast on Spotify to Improve Students' Listening Skills - Salsabila, Widya; Irianti, Leni; Thoyyibah, Luthfiyatun (Siliwangi University, 2021)
This research reported the issues of using Georgina's podcast on Spotify to improve students' listening skills. This research aimed at figure out the improvement of the students' listening ability in listening skills by using the Spotify application as a tool that focused on listening to Georgina's podcast in subject asking and giving directions. In doing so, the subjects consisted of 20 students who were in tenth grade. The researcher applied a mixed methods design, which type is the embedded design. The instruments were a test and a questionnaire. The sample was taken by using a random sampling technique. The results of the test and the related comparisons, findings showed that Georgina's podcast on Spotify is effective to improve students' listening skills. This can be seen from the mean results of the pre-test was 30.00 and the post-test was 86.67 with the t-test value orientation is greater than the t-table (12.3912.110). As a result of this fact, the post-test score in the class was significantly different after going under the treatment. To sum up, Georgina's podcast on Spotify is an effective medium to improve students' listening skills in subject asking and giving directions. However, the success of podcasting depends on the teacher's ability to use Spotify and the selection of appropriate material in a way that guides students to achieve their learning goals.